Aqueous high-solid composite conductive liquid and its preparation method and application
By developing water-based high-solid composite conductive liquid in sodium ion batteries, the synergistic effects of carbon nanotubes, carbon black and graphene are used to solve the problem of poor conductivity of polyanionic compounds, and the performance improvement of high conductivity and low-cost battery performance is achieved.
Patent Information
- Application Number
- CN202411954591.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
In existing sodium ion batteries, the polyanionic compound materials of the water-based positive electrode conducting liquid have poor conductivity, which limits the rate performance and energy density of the battery. In addition, the traditional oil system uses the organic solvent NMP, which is costly and not environmentally friendly.
A water-based high-solid-containing composite conductive liquid was developed. By treating the synergistic effects of carbon nanotubes, carbon black and graphene in a ball mill and a sand mill, a conductive liquid with high solid content and good fluidity was prepared. It was used as the positive electrode slurry conductive agent for sodium ion batteries to replace the traditional oil system.
The high conductivity, low addition amount and high flowability of sodium ion batteries are achieved, improving the rate performance and energy density of the battery, while reducing costs and improving environmental protection and safety.
Smart Images

Figure CN119764451A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to an aqueous high-solid-content composite conductive liquid and a preparation method and application thereof. Background Art
[0002] Lithium batteries have excellent performance and have always been the dominant battery system. However, in recent years, the price of lithium carbonate has soared, and the cost of lithium batteries has increased significantly, which has put pressure on the industrial chain. As a result, companies are seeking new material systems to make breakthroughs. Sodium batteries (sodium-ion batteries) have become the first choice due to their natural cost advantages. At the same time, the domestic supply of sodium carbonate is sufficient, and the supply chain is safer. With the investment of all parties in the research and development of sodium batteries, the research and development of sodium batteries has progressed rapidly, and sodium battery technology and materials have gradually become possible for industrialization. It is expected that it will first replace lead-acid batteries in the future, and gradually enter the A00-class electric vehicles and energy storage fields. It is expected to become an effective supplement to lithium batteries in the future.
[0003] The positive electrode conductive agent is one of the key factors that determine the performance of the battery. However, the current traditional positive electrode conductive slurry mostly uses an oil system with NMP (N-methylpyrrolidone) as an organic solvent to match the battery slurry process. The solvent is used in large quantities, is not easy to recycle, and has high costs. It also causes great pollution to the ecological environment. Therefore, the preparation of low-cost, green and pollution-free aqueous positive electrode conductive slurry has become a technical difficulty that battery professionals are eager to solve. At present, the mature positive electrode materials in the field of sodium batteries are layered transition metal oxides, Prussian blue compounds and polyanion compounds. Among them, the polyanion compound (sodium vanadium phosphate) has an olivine stable structure similar to lithium iron phosphate, so an aqueous sodium vanadium phosphate slurry solution can be used. However, polyanion compounds generally have poor conductivity, so the rate performance is poor and the energy density is low.
[0004] In summary, the sodium-ion battery market has broad prospects, but the polyanion compound materials currently suitable for its aqueous slurry have poor conductivity, which limits the battery's rate performance and energy density. Therefore, it is necessary to develop a conductive liquid that can be applied to the positive electrode slurry to improve the conductivity of the sodium-ion battery, which is green and environmentally friendly and can greatly reduce costs. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an aqueous high-solid composite conductive liquid and its preparation method and application. The aqueous composite conductive liquid provided by the present invention has the advantages of high solid content, good fluidity, low addition amount and high conductivity in the aqueous sodium ion battery system.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an aqueous high-solid composite conductive liquid, wherein the raw materials for preparing the aqueous high-solid composite conductive liquid include the following components in terms of weight percentage:
[0008]
[0009] The composite conductive liquid provided by the present invention has a high solid content (solid content ≥ 10%), good fluidity, and is easy to disperse. As a conductive agent for the aqueous positive electrode slurry of a sodium battery, it can improve the stability and poor castability of the slurry with a low addition amount, high conductivity, and high fluidity; at the same time, it is added as a conductive agent to the aqueous positive electrode slurry to prepare the positive electrode slurry, and assembled into a button cell for electrical performance testing, and compared with the button cell prepared from the same type of oil-based positive electrode slurry for electrical performance, its cycle performance and rate performance are not much different from those of the same type of oil-based positive electrode slurry. In addition, the present invention uses low-cost deionized water to replace the organic solvent NMP, which is more expensive, polluting the environment, and harmful to human health. While maintaining electrical performance, it can greatly reduce costs and improve safety. In addition, the composite conductive liquid provided by the present invention can achieve low addition amount and high coverage.
[0010] The carbon tubes selected for the composite conductive liquid provided by the present invention are winding tubes with high cost performance. The synergistic effect of carbon nanotubes, graphene and carbon black ensures that the slurry has long-term stability under high flow. After aqueous slurry mixing, a three-dimensional conductive system network is formed in the battery system, which is beneficial to the performance of the rate performance of the polyanion material.
[0011] In the present invention, the solid content of the composite conductive liquid refers to the sum of the contents of other components except ionized water.
[0012] In the present invention, the raw materials for preparing the aqueous high solid content composite conductive liquid can be 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, etc. in terms of weight percentage; the amount of carbon black can be 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, etc.; the amount of graphene can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%. , 2.3%, 2.4%, 2.5% and the like; the amount of dispersant can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% and the like; the amount of regulator can be 0.05%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2% and the like; the balance is deionized water.
[0013] Preferably, the dispersant includes any one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, and Triton-100, or a combination of at least two thereof.
[0014] Preferably, the modulator comprises AMP-95.
[0015] In a second aspect, the present invention provides a method for preparing the aqueous high-solid composite conductive liquid as described in the first aspect, the preparation method comprising the following steps:
[0016] (1) mixing the formulated amount of dispersant, regulator, and deionized water in a stirrer to obtain a glue solution;
[0017] (2) Dividing the glue liquid obtained in step (1) into two equal parts, adding one of the glue liquid, carbon nanotubes and carbon black into a ball mill, and then adding the ball-milled materials into a sand mill, and then sand milling them to obtain a uniform and stable first semi-finished conductive liquid;
[0018] (3) mixing another portion of the glue liquid with the graphene, and then homogenizing the mixed materials to obtain a second semi-finished conductive liquid;
[0019] (4) The first semi-finished conductive liquid and the second semi-finished conductive liquid are mixed and dispersed to obtain the aqueous high-solid composite conductive liquid.
[0020] The preparation method provided by the present invention adopts a processing route of ball milling, sand milling and homogenization, and adjusts the processing time, so that the prepared composite conductive liquid still has a good dispersion effect under the condition of high solid content, so that it can be used in sodium ion batteries, and the sodium ion batteries can have better electrical properties.
[0021] Preferably, the gluing time in step (1) is 30-120 min, for example, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.
[0022] Preferably, the ball milling time in step (2) is 1 to 5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, etc.
[0023] Preferably, the sanding time in step (2) is 1 to 5 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.
[0024] Preferably, the mixing in step (3) is carried out in a high-speed stirrer.
[0025] Preferably, the homogenization time in step (3) is 1 to 5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, etc.
[0026] Preferably, the dispersion in step (4) is high-speed dispersion.
[0027] Preferably, the dispersion time in step (4) is 1 to 2 hours, such as 1 hour, 1.5 hours, 2 hours, etc.
[0028] In a third aspect, the present invention provides a use of the aqueous high-solid composite conductive liquid as described in the first aspect in a sodium ion battery.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention limits the amount of carbon nanotubes, carbon black and graphene used, and obtains a water-based high-solid composite conductive liquid with high conductivity and high fluidity through a processing route of ball milling, sand milling and homogenization. The liquid is used as a conductive agent and added in a low amount to a water-based positive electrode slurry to prepare a positive electrode slurry, which is then assembled into a sodium ion battery. The sodium ion battery has better conductivity, and the battery rate and cycle performance are not much different from the electrical performance of a sodium ion battery prepared from the same type of oil-based positive electrode slurry. While maintaining the electrical performance, the cost can be greatly reduced and personal safety and environmental safety can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The SEM images of the carbon nanotube powders used in the examples and comparative examples of the present invention are shown in FIG.
[0032] Figure 2 The following are SEM images of graphene powders used in the embodiments and comparative examples of the present invention.
[0033] Figure 3 This is a SEM image of the first semi-finished conductive liquid provided in Example 1.
[0034] Figure 4 This is a SEM image of the aqueous high-solid composite conductive liquid provided in Example 1.
[0035] Figure 5 This is a SEM image of the first semi-finished conductive liquid provided in Comparative Example 1.
[0036] Figure 6 This is the SEM image of the oil-based high-solid composite conductive liquid provided in Comparative Example 1.
[0037] Figure 7 This is a graph of the rate performance test results of the sodium ion battery provided for Application Example 1.
[0038] Figure 8This is a graph showing the rate performance test results of the sodium ion battery provided for comparative application example 1.
[0039] Fig. 9 A comparison chart of normal temperature cycling results of the sodium ion battery provided for Application Example 1 and Comparative Application Example 1 at 0.5C. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0041] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present invention are as follows:
[0042] Carbon nanotube powder: Use relatively low-cost winding tubes. The average diameter of carbon nanotubes is 10-15nm and the average length is 50-80μm. The SEM image of carbon nanotube powder is as follows: Figure 1 As shown;
[0043] Carbon black: KABOTE LITX35R;
[0044] Graphene powder: YH-200; SEM image of graphene powder is as follows Figure 2 shown.
[0045] Example 1
[0046] In this embodiment, an aqueous high-solid composite conductive liquid is provided. The raw materials for preparing the aqueous high-solid composite conductive liquid include the following components in terms of weight percentage:
[0047]
[0048] Wherein, the dispersant is polyvinyl pyrrolidone (K30) and the regulator is AMP-95.
[0049] The preparation method comprises the following steps:
[0050] (1) mixing the formulated amount of dispersant, regulator and deionized water in a stirrer for 90 minutes to obtain a glue solution;
[0051] (2) Dividing the glue liquid obtained in step (1) into two equal parts, adding one of the glue liquid, carbon nanotube powder and carbon black into a ball mill, and ball milling for 3 hours, and then adding the ball-milled materials into a sand mill, and sand milling for 3 hours to obtain a uniform and stable first semi-finished conductive liquid;
[0052] (3) fully dispersing another portion of the glue solution and the graphene powder in a high-speed stirrer, and then homogenizing the dispersed materials for 3 hours to obtain a second semi-finished conductive liquid;
[0053] (4) The first semi-finished conductive liquid and the second semi-finished conductive liquid are mixed and dispersed at 1500 rpm for 1.5 hours to obtain the aqueous high-solid composite conductive liquid.
[0054] Example 2
[0055] In this embodiment, an aqueous high-solid composite conductive liquid is provided. The raw materials for preparing the aqueous high-solid composite conductive liquid include the following components in terms of weight percentage:
[0056]
[0057] Wherein, the dispersant is polyvinyl pyrrolidone (K30) and the regulator is AMP-95.
[0058] The preparation method comprises the following steps:
[0059] (1) mixing the formulated amount of dispersant, regulator and deionized water in a stirrer for 30 minutes to obtain a glue solution;
[0060] (2) The glue liquid obtained in step (1) is evenly divided into two parts, one of which is added into a ball mill with carbon nanotube powder and carbon black, and ball milled for 1 hour, and then the ball-milled material is added into a sand mill and sand milled for 1 hour to obtain a uniform and stable first semi-finished conductive liquid;
[0061] (3) fully dispersing another portion of the glue solution and the graphene powder in a high-speed stirrer, and then homogenizing the dispersed materials for 1 hour to obtain a second semi-finished conductive liquid;
[0062] (4) The first semi-finished conductive liquid and the second semi-finished conductive liquid are mixed and dispersed at 1500 rpm for 1 hour to obtain the aqueous high-solid composite conductive liquid.
[0063] Example 3
[0064] In this embodiment, an aqueous high-solid composite conductive liquid is provided. The raw materials for preparing the aqueous high-solid composite conductive liquid include the following components in terms of weight percentage:
[0065]
[0066] Wherein, the dispersant is polyvinyl pyrrolidone (K30) and the regulator is AMP-95.
[0067] The preparation method comprises the following steps:
[0068] (1) mixing the formulated amount of dispersant, regulator and deionized water in a stirrer for 120 minutes to obtain a glue solution;
[0069] (2) Dividing the glue liquid obtained in step (1) into two equal parts, adding one of the glue liquid, carbon nanotube powder and carbon black into a ball mill, and ball milling for 5 hours, and then adding the ball-milled materials into a sand mill, and sand milling for 5 hours to obtain a uniform and stable first semi-finished conductive liquid;
[0070] (3) fully dispersing another portion of the glue solution and the graphene powder in a high-speed stirrer, and then homogenizing the dispersed materials for 5 hours to obtain a second semi-finished conductive liquid;
[0071] (4) The first semi-finished conductive liquid and the second semi-finished conductive liquid are mixed and dispersed at 1500 rpm for 2 hours to obtain the aqueous high-solid composite conductive liquid.
[0072] Example 4
[0073] In this embodiment, an aqueous high-solid composite conductive liquid is provided. The raw materials for preparing the aqueous high-solid composite conductive liquid include the following components in terms of weight percentage:
[0074]
[0075]
[0076] Wherein, the dispersant is polyvinyl pyrrolidone (K30) and the regulator is AMP-95.
[0077] The preparation method comprises the following steps:
[0078] (1) mixing the formulated amount of dispersant, regulator and deionized water in a stirrer for 60 minutes to obtain a glue solution;
[0079] (2) The glue liquid obtained in step (1) is evenly divided into two parts, one of which is added into a ball mill with carbon nanotube powder and carbon black, and ball milled for 2 hours, and then the ball-milled material is added into a sand mill and sand milled for 4 hours to obtain a uniform and stable first semi-finished conductive liquid;
[0080] (3) fully dispersing another portion of the glue solution and the graphene powder in a high-speed stirrer, and then homogenizing the dispersed materials for 2 hours to obtain a second semi-finished conductive liquid;
[0081] (4) The first semi-finished conductive liquid and the second semi-finished conductive liquid are mixed and dispersed at 1500 rpm for 1.5 hours to obtain the aqueous high-solid composite conductive liquid.
[0082] Example 5
[0083] In this embodiment, an aqueous high-solid composite conductive liquid is provided. The raw materials for preparing the aqueous high-solid composite conductive liquid include the following components in terms of weight percentage:
[0084]
[0085]
[0086] Wherein, the dispersant is polyvinyl pyrrolidone (K30) and the regulator is AMP-95.
[0087] The preparation method comprises the following steps:
[0088] (1) mixing the formulated amount of dispersant, regulator and deionized water in a stirrer for 90 minutes to obtain a glue solution;
[0089] (2) The glue liquid obtained in step (1) is evenly divided into two parts, one of which is added into a ball mill with carbon nanotube powder and carbon black, and ball milled for 4 hours, and then the ball-milled material is added into a sand mill and sand milled for 2 hours to obtain a uniform and stable first semi-finished conductive liquid;
[0090] (3) fully dispersing another portion of the glue solution and the graphene powder in a high-speed stirrer, and then homogenizing the dispersed materials for 4 hours to obtain a second semi-finished conductive liquid;
[0091] (4) The first semi-finished conductive liquid and the second semi-finished conductive liquid are mixed and dispersed at 1500 rpm for 1.5 hours to obtain the aqueous high-solid composite conductive liquid.
[0092] Comparative Example 1
[0093] The only difference between this comparative example and Example 1 is that the deionized water is replaced by an equal weight of NMP (N-methylpyrrolidone), that is, this comparative example provides an oil-based high-solid composite conductive liquid.
[0094] Comparative Example 2
[0095] The only difference between this comparative example and Example 1 is that step (2) does not include a ball milling step.
[0096] Comparative Example 3
[0097] The only difference between this comparative example and Example 1 is that step (2) does not include a sanding step.
[0098] Comparative Example 4
[0099] The only difference between this comparative example and Example 1 is that step (3) does not include a homogenization step.
[0100] Comparative Example 5
[0101] The only difference between this comparative example and Example 1 is that the sum of the weight percentages of carbon nanotube powder, carbon black and graphene powder is 4%, wherein the weight percentages of carbon nanotube powder, carbon black and graphene powder are 0.96%, 2.24% and 0.8% respectively.
[0102] The SEM image of the first semi-finished conductive liquid provided in Example 1 of the present invention is as follows: Figure 3 As shown, the SEM image of the aqueous high solid content composite conductive liquid is as follows Figure 4 As shown; the SEM image of the first semi-finished conductive liquid provided in Comparative Example 1 is as shown Figure 5 As shown, the SEM image of the oil-based high solid content composite conductive liquid is as follows Figure 6 As shown; it can be seen that the SEM image of the water-based high-solid-content composite conductive liquid provided by the present invention is not much different from the SEM image of the oil-based high-solid-content composite conductive liquid.
[0103] Application Example 1
[0104] In this application example, a sodium ion battery is provided, and the materials are as follows: the positive electrode is sodium vanadium phosphate (NVP); the negative electrode is hard carbon CARBOTRON PJ; the electrolyte formula is as follows: NaPF6 is dissolved in a mixed solution of EC, EMC, and DMC (wherein the volume ratio of EC, EMC, and DMC is 1:1:1, and the concentration of NaPF6 in the mixed solution is 1.0M), and VC is added, and the amount of VC added is 1% of the total mass of EC, EMC, and DMC;
[0105] NVP, CMC, SBR and the aqueous high-solid composite conductive liquid provided in Example 1 are mixed to obtain a positive electrode slurry, wherein NVP: CMC: SBR: CNT = 94.8%: 1.2%: 2.5%: 1.5% (mass ratio), wherein CNT refers to the total of carbon nanotubes, carbon black and graphene;
[0106] Mix hard carbon, SP, CMC and SBR to obtain a negative electrode slurry, wherein hard carbon: SP: CMC: SBR = 95.2%: 1.0%: 1.8%: 2.0% (mass ratio);
[0107] The solid content of the positive electrode slurry is 51%, and the solid content of the negative electrode slurry is 50%. The slurry is made into pole pieces through a doctor blade transfer coater, and then assembled into 554065-1.5Ah batteries through cutting, winding and assembly processes.
[0108] Application Examples 2-5, Comparative Application Examples 1-5
[0109] The only difference from Application Example 1 is that the composite conductive liquid is replaced with an equal amount of the composite conductive liquid provided in Examples 2-5 and Comparative Examples 1-5.
[0110] The performance test of the sodium ion battery provided in the corresponding use case and comparative application example is carried out. The test method is as follows:
[0111] (1) Rate performance: In the voltage range of 2.4-3.55, the battery is charged at 0.5C current and discharged at rates of 0.5C, 1C, 2C and 3C to test the rate performance of the battery;
[0112] (2) Cycle performance: The battery was charged at 0.5C current and discharged at 0.5C rate current in the voltage range of 2.4-3.55 to test the cycle performance.
[0113] The performance test results are shown in Table 1.
[0114] Table 1
[0115]
[0116] It can be seen from Table 1 that the performance of the sodium ion battery prepared by the water-based composite conductive liquid provided by the embodiment of the present invention is comparable to that of the sodium ion battery prepared by the same type of oil-based composite conductive liquid (Comparative Application Example 1), but the composite conductive liquid provided by the present invention is green and environmentally friendly, greatly reducing costs and improving safety.
[0117] Compared with Application Example 1, except for Comparative Application Example 1 whose rate performance is comparable to that of Application Example 1, the sodium ion batteries provided by other comparative application examples perform slightly worse in 1C, 2C and 3C rate tests.
[0118] The rate performance test results of the sodium ion battery provided in Application Example 1 of the present invention are shown in the figure below: Figure 7 shown.
[0119] The rate performance test results of the sodium ion battery provided by the comparative application example 1 of the present invention are shown in the figure below: Figure 8 shown.
[0120] The comparison results of the normal temperature cycle of the sodium ion battery provided by Application Example 1 of the present invention and Comparative Application Example 1 at 0.5C are shown in the figure Fig. 9 As shown. Figure 7-Figure 9 It can also be seen that the performance of the sodium ion battery prepared by using the water-based composite conductive liquid provided in the embodiment of the present invention is comparable to that of the sodium ion battery prepared by using the same type of oil-based composite conductive liquid (Comparative Application Example 1).
[0121] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the aqueous high-solid composite conductive liquid and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An aqueous high solid content composite conductive liquid, characterized in that: The raw materials for preparing the aqueous high solid content composite conductive liquid include the following components in terms of weight percentage:
2. The aqueous high-solid composite conductive liquid according to claim 1, characterized in that: The dispersant includes any one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and Triton-100, or a combination of at least two of them.
3. The aqueous high-solid composite conductive liquid according to claim 1 or 2, characterized in that: Such modulators include AMP-95.
4. A method for preparing an aqueous high-solid composite conductive liquid according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing the formulated amount of dispersant, regulator, and deionized water in a blender to obtain a glue solution; (2) Dividing the glue liquid obtained in step (1) into two equal parts, adding one of the glue liquid, carbon nanotubes and carbon black into a ball mill, and then adding the ball-milled materials into a sand mill, and then sand milling them to obtain a first semi-finished conductive liquid; (3) mixing another portion of the glue liquid with the graphene, and then homogenizing the mixed materials to obtain a second semi-finished conductive liquid; (4) The first semi-finished conductive liquid and the second semi-finished conductive liquid are mixed and dispersed to obtain the aqueous high-solid composite conductive liquid.
5. The preparation method according to claim 4, characterized in that: The gluing time in step (1) is 30-120 minutes.
6. The preparation method according to claim 4 or 5, characterized in that: The ball milling time in step (2) is 1 to 5 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The sand grinding time in step (2) is 1 to 5 hours.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The mixing in step (3) is carried out in a high-speed stirrer; Preferably, the homogenization time in step (3) is 1 to 5 hours.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The dispersion time in step (4) is 1 to 2 hours.
10. Use of the aqueous high-solid composite conductive liquid according to any one of claims 1 to 3 in a sodium ion battery.